Analysis of The Effectiveness and Efficiency of Working Capital on LPD in Dalung Village - Ade Aprilia Arta Sari; I M Sudana; I M D J Sulastra (Jurusan Akuntansi Politeknik Negeri Bali, 2020)
The purpose of this study was to determine the effectiveness of working capital use in terms of cash turnover ratios and receivable turnover ratios and to determine the efficiency of working capital use in the LPD Dalung Village. The analysis technique used in this study is quantitative and qualitative analysis. Based on the results of the analysis conducted shows the effectiveness of working capital use when viewed from the ratio of cash turnover, which in 2015 was considered less effective, in 2016 was considered quite effective, in 2017 was considered very effective, and in 2018-2019 it was considered quite effective. Meanwhile, if seen from the receivable turnover ratio, where in 2015 was considered very effective, in 2016, 2017, 2018 was considered quite effective, and in 2019 it was considered less effective. The efficiency of using working capital from 2015-2019 when viewed from the working capital turnover ratio, where in 2015 was considered very efficient, in 2016, 2017, 2018 and 2019 it was considered quite efficient. Whereas if seen from the profit ratio, which in 2015 was considered very efficient, in 2016, 2017 and 2018 it was considered quite efficient, and in 2019 it was considered less efficient.